2015
DOI: 10.1039/c5cp01241d
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the structure of nanocomposites of triglyceride platelets and DNA

Abstract: DNA-complexes with platelet-like, cationically modified lipid nanoparticles (cLNPs) are studied with regard to the formation of nanocomposite structures with a sandwich-like arrangement of the DNA and platelets. For this purpose suspensions of platelet-like triglyceride nanocrystals, stabilized by a mixture of two nonionic (lecithin plus polysorbate 80 or poloxamer 188) and one cationic stabilizer dimethyldioctadecylammonium (DODAB), are used. The structure of the platelets in the native suspensions and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
(112 reference statements)
0
3
0
Order By: Relevance
“…The first sample is an aqueous suspension of platelet-shaped tripalmitin nanocrystals (TP NCs). Corresponding systems of TP NCs have been intensively studied by our group (Schmiele et al, 2015;Schmiele, Gehrer et al, 2014) as potential drug delivery systems. The second sample is an aqueous dispersion of commercial silica particles (Ludox TM50, 50 wt%) purchased from Sigma-Aldrich; the average diameter of the SiO 2 NPs is about 26 AE 2 nm (see fitting results in Fig.…”
Section: Performance Evaluation Of the Portable Saxs Systemmentioning
confidence: 99%
“…The first sample is an aqueous suspension of platelet-shaped tripalmitin nanocrystals (TP NCs). Corresponding systems of TP NCs have been intensively studied by our group (Schmiele et al, 2015;Schmiele, Gehrer et al, 2014) as potential drug delivery systems. The second sample is an aqueous dispersion of commercial silica particles (Ludox TM50, 50 wt%) purchased from Sigma-Aldrich; the average diameter of the SiO 2 NPs is about 26 AE 2 nm (see fitting results in Fig.…”
Section: Performance Evaluation Of the Portable Saxs Systemmentioning
confidence: 99%
“…Submicron-sized solid lipid particles have been proposed for parenteral drug delivery carrier systems by Westesen and Siekmann in 1992. , Detailed studies of the properties of such first generation solid lipid nanoparticles (SLNs) with their complex mesoscopic (length scale between ∼1 nm and some microns) structure have been published subsequently (cf., e.g., refs ). It has been found that the maximum uptake for drugs by the SLNs is very limited in general due to their essentially crystalline nature. , Nanostructured lipid carriers (NLCs) are still solid nanoparticles but their core consists of a mixture of solid and liquid lipids .…”
Section: Introductionmentioning
confidence: 99%
“…To eventually understand the underlying particle formation and stabilization processes, it is reasonable to first conduct comprehensive structural investigations of final NPs prior to in situ studies. The combination of small-angle X-ray and neutron scattering (SAXS, SANS) studies has been proven to be a powerful tool for the molecular characterization of the stabilizing layer of dispersed organic and inorganic NPs. For instance, the structures of nanosized lecithin-stabilized tetracosane lipid emulsions and suspensions produced by HPH were extensively investigated by SAXS and SANS. , The thickness of the lecithin layer was found to be 0.16 and 0.105 nm for the emulsion and the suspension, respectively, while no penetration of tetracosane molecules into the stabilizer layer could be observed. Studies on the size, morphology, and bioavailability of NPs prepared by AP exist. , The impact of AP on the molecular structure as well as the particle formation and stabilization process are, however, still not well understood, nor is the achievement of small particle sizes trivial.…”
Section: Introductionmentioning
confidence: 99%